2012
DOI: 10.1017/s1355617712000276
|View full text |Cite
|
Sign up to set email alerts
|

Increased Marijuana Use and Gender Predict Poorer Cognitive Functioning in Adolescents and Emerging Adults

Abstract: This study sought to characterize neuropsychological functioning in MJ-using adolescents and emerging adults (ages 18–26) and to investigate whether gender moderated these effects. Data were collected from 59 teens and emerging adults including MJ users (n = 23, 56% female) and controls (n = 35, 50% female) aged 18–26 (M = 21 years). Exclusionary criteria included independent Axis I disorders (besides SUD), and medical and neurologic disorders. After controlling for reading ability, gender, subclinical depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
136
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 84 publications
(149 reference statements)
12
136
1
Order By: Relevance
“…Our results complement previous research using both correlation and regression analyses to address the role of marijuana use variables. Earlier age at marijuana onset has previously been shown to correlate with impaired performance on the Stroop and WCST tasks (Battisti et al, 2010;Gruber et al, 2012b), whereas increased frequency and magnitude of marijuana use have been shown to be related to impairment in psychomotor speed, sustained attention, and cognitive inhibition (Lisdahl & Price, 2012), as well as verbal memory (Solowij et al, 2011) and executive function (Gruber et al, 2012b;Harvey et al, 2007). In addition, this study incorporated logistic regression techniques and demonstrated that increased total perseverative errors on the WCST is a moderately accurate predictor of marijuana smokers, suggesting that this may be a clinical characteristic of chronic, heavy marijuana use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results complement previous research using both correlation and regression analyses to address the role of marijuana use variables. Earlier age at marijuana onset has previously been shown to correlate with impaired performance on the Stroop and WCST tasks (Battisti et al, 2010;Gruber et al, 2012b), whereas increased frequency and magnitude of marijuana use have been shown to be related to impairment in psychomotor speed, sustained attention, and cognitive inhibition (Lisdahl & Price, 2012), as well as verbal memory (Solowij et al, 2011) and executive function (Gruber et al, 2012b;Harvey et al, 2007). In addition, this study incorporated logistic regression techniques and demonstrated that increased total perseverative errors on the WCST is a moderately accurate predictor of marijuana smokers, suggesting that this may be a clinical characteristic of chronic, heavy marijuana use.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a longer period of marijuana abstinence was not utilized because studies using longer periods of abstinence (e.g. 7 days of abstinence [Lisdahl & Price, 2012] and 28 days of abstinence [Pope et al, 2003]) are more likely assessing cognitive function related to cessation of marijuana use. Instead, the 12-hour abstinence period was implemented to accurately reflect the impact of regular use on cognitive function in a naturalistic sample of current marijuana smokers.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interconnectedness of mental health problems, persistent cannabis use, and neuropsychological functioning demands more careful attention, and the literature (12,13) suggests the value of controlling for more than just schizophrenia (as did Meier et al). Similarly, potential sex differences require closer scrutiny, given accumulating evidence that nonacute or persistent cannabis use may have differing effects on neurocognitive functioning of males and females (14)(15)(16)(17). Sex differences in brain cannabinoid receptor density, endocrine modulation of endocannabinoid activity, tolerance, and tetrahydrocannabinol metabolism may all contribute to these differences (18,19).…”
mentioning
confidence: 99%
“…Alcohol consumption was not reported and biochemical assays were not undertaken to confirm self-reports. Future studies may consider more detailed assessment of recent consumption to rule out potential influence of acute usage and withdrawal on cognitive performance (Lisdahl and Price, 2012). The neurocognitive tests were presented in a fixed order between subjects.…”
Section: Limitationsmentioning
confidence: 99%